Optimalisasi Strategi Bisnis UMKM: Analisis SWOT dan QSPM pada Yoga Barbershop di Palaran - Diyaa Aaisyah Salmaa Putri Atmaja; Purbawati Purbawati; Adhe Dalle Tri Saputro; Desi Puspitasari; Muhammad Syarif; Muhammad Ilham Syahranie; Salma Maulina Wardhani (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study ais to formulate development strategies for Yoga Barbershop in Palaran, East Kalimantan, using SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM). SWOT analysis is utilized to assess internal and external factors,combned with QSPM to determine priority strategies. The study reveals that Yoga Barbershop’s strengths nclude customer loyalty, a strategic location, modern haircut styles,and ownership of the business premises, which reduces operational costs.However, identified weaknesses consist of limited service facilities, inflexible operating hours, restricted space, noise issues, and insufficient staff. Meanwhile, opportunities for Yoga Barbershop include opening new braches and recruiting additional employees. Threats arise from similiar business competitors and changes in hairstyle trends. Based on the findings, Yoga Barbershop’s IE matrix places the business in quadrant V, with a total IFE score of 2,72 and an EFE score of 2,71, indicating a stable position that requires stability strategies. The recommended strategy is the weakness-opportunity (WO) approach. Priority strategic recommendations, in order of importance, are opening a new branch, training new staff, and increasing the flexibility of operational hours.